Interpretation of Hadith Regarding Ihtikar (Monopoly) In the Perspective of Contemporary Sharia Economic Law - Elma Kamala; HM. Ridlwan Hambali; Ayu Nur Chamidah (AL-DZIKRA: JURNAL STUDI ILMU AL-QUR'AN DAN AL-HADITS, 2026)
Abstract The current global economy faces serious challenges in market mechanisms, including the dominance of large corporations, supply chain distortions, price manipulation, and distribution control by certain entities. This phenomenon bears substantive similarity to the concept of ihtikar in Islam, namely the act of withholding goods to create scarcity and raise prices, thereby causing hardship for the community. Prophetic traditions (ḥadīth) such as "lā yaḥtakiru illā khāṭi'" and "man dakhala fī siʿrinā liyughliyahu 'alaynā fahuwa minnā laysa minnā" affirm a clear prohibition against practices that disrupt market equilibrium. Through a qualitative-descriptive approach and comparative analysis, this study examines the views of classical scholars such as al-Nawawī, Ibn Taymiyyah, and Ibn Ḥajar, and then connects them to contemporary thought on maqāṣid al-sharī'ah, particularly the values of justice ('adl), public interest (al-maṣlaḥah al-'āmmah), and the protection of property (ḥifẓ al-māl). The findings indicate that the essence of the prohibition of ihtikar is highly relevant to the principles of modern price policies such as competition law, anti-trust regulation, and market oversight. Islamic teachings align with the objectives of contemporary regulations to prevent market exploitation, maintain price stability, and protect consumers from economic distortion. Thus, the ḥadīth prohibiting ihtikar possess not only moral and spiritual dimensions but also provide a normative framework for formulating just, inclusive, and public welfare-oriented modern economic policies. Keywords: Ihtikar; Maqashid Syariah; Contemporary Sharia economic Law.   Abstrak Ekonomi global saat ini menghadapi tantangan serius pada mekanisme pasar, berupa dominasi korporasi besar, distorsi rantai pasok, manipulasi harga, dan penguasaan distribusi oleh entitas tertentu. Fenomena ini memiliki kemiripan substantif dengan konsep ihtikar dalam Islam, yaitu tindakan menahan barang untuk menciptakan kelangkaan dan menaikkan harga sehingga menimbulkan kesulitan bagi masyarakat. Hadis-hadis seperti "lā yaḥtakiru illā khāṭi'" dan "man dakhala fī siʿrinā liyughliyahu 'alaynā fahuwa minnā laysa minnā" menegaskan larangan tegas terhadap praktik yang merusak keseimbangan pasar. Melalui pendekatan kualitatif-deskriptif dan analisis komparatif, penelitian ini menelaah pandangan ulama klasik seperti al-Nawawi, Ibn Taymiyyah, dan Ibn Hajar, kemudian menghubungkannya dengan pemikiran kontemporer mengenai maqāṣid al-syarī'ah, terutama nilai keadilan ('adl), kemaslahatan umum (al-maslahah al-'āmmah), dan perlindungan harta (ḥifẓ al-māl). Temuan penelitian menunjukkan bahwa substansi larangan ihtikar sangat relevan dengan prinsip-prinsip kebijakan harga modern seperti competition law, anti-trust regulation, dan pengawasan pasar. Ajaran Islam sejalan dengan tujuan regulasi kontemporer untuk mencegah eksploitasi pasar, menjaga stabilitas harga, serta melindungi konsumen dari distorsi ekonomi. Dengan demikian, hadis-hadis tentang larangan ihtikar tidak hanya memiliki dimensi moral dan spiritual, tetapi juga menyediakan kerangka normatif bagi perumusan kebijakan ekonomi modern yang adil, inklusif, dan berorientasi pada kesejahteraan publik. Kata Kunci: Ihtikar; Maqashid Syariah; Hukum ekonomi Syariah Kontemporer.